Rapid specialization of counter defenses enables two-spotted spider mite to adapt to novel plant hosts. Issue 4 (31st August 2021) - Salehipourshirazi, Golnaz; Bruinsma, Kristie; Ratlamwala, Huzefa; Dixit, Sameer; Arbona, Vicent; Widemann, Emilie; Milojevic, Maja; Jin, Pengyu; Bensoussan, Nicolas; Gómez-Cadenas, Aurelio; Zhurov, Vladimir; Grbic, Miodrag; et al.
Abstract: Genetic adaptation, occurring over a long evolutionary time, enables host-specialized herbivores to develop novel resistance traits and to efficiently counteract the defenses of a narrow range of host plants. In contrast, physiological acclimation, leading to the suppression and/or detoxification of host defenses, is hypothesized to enable broad generalists to shift between plant hosts. However, the host adaptation mechanisms used by generalists composed of host-adapted populations are not known. Two-spotted spider mite (TSSM; Tetranychus urticae ) is an extreme generalist herbivore whose individual populations perform well only on a subset of potential hosts. We combined experimental evolution, Arabidopsis thaliana genetics, mite reverse genetics, and pharmacological approaches to examine mite host adaptation upon the shift of a bean ( Phaseolus vulgaris )-adapted population to Arabidopsis. We showed that cytochrome P450 monooxygenases are required for mite adaptation to Arabidopsis. We identified activities of two tiers of P450s: general xenobiotic-responsive P450s that have a limited contribution to mite adaptation to Arabidopsis and adaptation-associated P450s that efficiently counteract Arabidopsis defenses. In approximately 25 generations of mite selection on Arabidopsis plants, mites evolved highly efficient detoxification-based adaptation, characteristic of specialist herbivores. This demonstrates that specialization to plant resistance traits can occur within the ecological timescale, enabling the TSSM to shift to novel plant hosts. Abstract : Mites can evolve highly efficient detoxification-based adaptation in approximately 25 generations on an initially unfavorable plant host, revealing that specialization can occur within the ecological timescale.